Catalytic Behaviors of Expansible Graphite in the Synthesis of Butyl Acetate - Xiu-Yan Pang (E-Journal of Chemistry)
The catalysis of expandable graphite EG for esterification has been studied. EG was prepared with KMnO4 as oxidant and H2SO4 as inserting reagent. Eexpanded volume，x-ray diffraction and energy dispersive analysis for EG were carried, and its catalytic activity was detected in the reaction of acetic acid with butanol. Influence of mole ratio of butanol and acetic acid, dosage of EG on ester yield were optimumed single factor experiments. The suitable esterification condition is: molar ratio of butanol to acetic acid keeps 1.6:1.0, mass of EG keeps 9.0% of the total mass of reactants; reaction keeping up 1.0 h at the boling point, and esterification rate of 98.2% can be achieved. The reuse ester yield is 86.6% for first reuse and 61.2% for the second reuse.